Implementation of Close Loop Speed Control with VVVF Control and Slip Regulation on LIM - Aditya, K.; Newwel, A. (Engineering, Technology & Applied Science Research, 2014)
Open loop VVVF control has the disadvantage of low output torque when working at low frequency and poor speed precision at different load conditions.Various performance-improving schemes have been proposed for the basic VVVF control by compensating slips occurring in the low frequency range and slips caused by changing loads. Numerous papers have been published on the close loop speed control of rotary induction motor. In this paper a close loop speed control with VVVF control and slip regulation has been implemented for LIM based conveyor belt test Rig which compensates the disadvantages of traditional Volts/Hz control. SIMULINK results are presented to validate the effectiveness of proposed scheme.